Spanish adaptation of the Career Pathways Survey (CPS) scale to measure the level of perception of the Glass Ceiling phenomenon - Chuco Aguilar, Victoria Judith (2023)
The phenomenon of the Glass Ceiling, which refers to the invisible barriers that hinder women's access to high-ranking positions, raises a series of implications related to gender discrimination, which need to be analyzed in the academic field. In this sense, this article adapts the Career Path Survey to Spanish in order to evaluate the dimensions of the Glass Ceiling in the organizational environment. It also analyzes the salary gap and the challenges posed by the existence of the Glass Ceiling phenomenon. Through this study it was possible to calculate the reliability of the 38-item scale after adapting it to Spanish. In addition, the results of the study improve the level of understanding of the obstacles faced by women in the workplace and provide recommendations for future research and intervention programs.